Agronomic profile of the vegetable properties of family farmers in Lavras and microregion, Minas Gerais (Research, Society and Development, 2020)
The cultivation of vegetables in Brazil, explored in a familiar way, has grown considerably, driven by the demand for healthy food. Vegetables can become more profitable and profitable when they are managed properly. Thus, the knowledge of the agronomic profile related to the ways in which cultivated species and crops are managed can direct strategies of sustainability and credibility before the market. In this context, the objective was to analyze the agronomic profile of the vegetable properties of family farmers in Lavras and the micro-region, Minas Gerais. For this, the methodology with participant observation was used, with visits to 20 rural properties, aiming to identify, through an interview, the daily life of the producers. It was found that the majority of olive growers are male, with 51.3 years old and 1.6 children on average. These producers were all literate, a fact that contributes to the understanding of the terms present in the inserts of phytosanitary products. However, it is emphasized that the producer needs to be guided on the use and conservation of personal protective equipment, to ensure safety during spraying. The areas destined to polyculture are small (2.8 ha) and maintained basically with family labor. Lesser diversity of pests was observed due to polyculture, which, in a way, contributes to the balance of the agro-ecosystem. The main marketing channel is open markets. The lack of technical assistance is still a bottleneck, as it prevents the optimization of the production process and reduces the competitiveness of family farming in the agricultural market.